Charakterystyka skutecznych alternatywnych programów nauczania... - Michels, Bob (Horyzonty Wychowania, 2017)
This article looks at some of the successful components and characteristics of Best Practices in the United States and analyzes why some programs work and why others do not. It also discusses non-conventional and antisocial youth who are in our schools as well as strategies to assist in resolving and changing their behaviors. Looking at predisposing factors leading to delinquency, antisocial behavior and criminal factors are also reviewed as well as characteristics of a successful teacher in an alternative school setting.